2017
DOI: 10.1111/jsr.12640
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of narcolepsy in Catalunya (Spain)

Abstract: Previous studies have estimated an overall prevalence for narcolepsy between 15 and 70 cases per 100 000 inhabitants. We aimed to estimate the prevalence of narcolepsy in Catalunya (Catalonia), a north-east region of Spain (7 424 754 inhabitants), on 31 December 2014 by identifying all living subjects diagnosed with narcolepsy. First, we identified patients diagnosed by one of the 13 sleep, paediatric or neurological departments that perform tests regularly to diagnose narcolepsy. In a second phase, we searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Worldwide prevalence estimates suggest that approximately 25-50 persons out of 100,000 are affected (Oyahon et al, 2002;Partinen & Kronholm, 2017). Some recent studies indicate, that narcolepsy may be less frequent (Tió et al, 2018). Narcolepsy potentially affects every aspect of daily life with considerable personal, social and economic consequences.…”
Section: Clinical Need For a Guidelinementioning
confidence: 99%
“…Worldwide prevalence estimates suggest that approximately 25-50 persons out of 100,000 are affected (Oyahon et al, 2002;Partinen & Kronholm, 2017). Some recent studies indicate, that narcolepsy may be less frequent (Tió et al, 2018). Narcolepsy potentially affects every aspect of daily life with considerable personal, social and economic consequences.…”
Section: Clinical Need For a Guidelinementioning
confidence: 99%
“…One recent study conducted in the Spanish region of Catalonia reported a prevalence similar to the one calculated in our analysis (5.2/100,000). 30 The above differences generally indicate a lower narcolepsy prevalence in Germany, but they may also be due to our methodology, which required at least one inpatient diagnosis or two confirmed outpatient diagnoses of a specialist for inclusion in the analyses. We followed a more conservative approach because we aimed to avoid the inclusion of patients with misdiagnoses or incorrect documentation.…”
Section: Discussionmentioning
confidence: 89%
“…This may explain the discrepancy between the USA and Europe regarding the prevalence of NT2. In Europe, this is a tiny percentage of patients with narcolepsy, but in the USA, NT2 is a frequent diagnosis, probably 2 to 3 times as frequent as NT1 [9][10][11]. Since chronic sleep deprivation and shift work can cause this phenotype, it seems probable that the difference is mainly explained by the scrutiny of the exclusion of sleep deprivation as a cause.…”
Section: What Prevents Us From Having An Ideal Classification?mentioning
confidence: 99%